Accounting Enforcement and Bank Transparency under Hierarchical Supervision in a Banking Union - Bischof, Jannis; Elfers, Ferdinand; Rudolf, Nicolas (The Accounting Review, 2026)
ABSTRACT Banks often adjust their financial reporting in response to supervisory intervention. However, many banks operate under multiple supervisors with varying preferences. We examine how banks respond to such conflicting oversight within the European Banking Union, where the European Central Bank (ECB) is the central authority. The ECB’s Asset Quality Review revealed that its preferred asset valuations diverged from many banks’ IFRS-compliant practices that were previously accepted by local supervisors. Banks voluntarily aligned their reporting with the nonbinding preferences of the new central supervisor, although the adjustments varied across jurisdictions. Alignment was weaker when central and local supervisory objectives conflicted and stronger when joint supervision mitigated regulatory capture. Overall, these adjustments enhanced the informativeness of loan loss provisioning. With aligned reporting preferences across supervisory layers, the introduction of a central supervisor can thus significantly improve bank reporting and transparency, even without formal enforcement. Data Availability: The data used in this study are available from the sources identified in the manuscript. JEL Classifications: M41; M48; G20; G21; G28.